Assessment of the Methodology That Is Used to Determine the Nutritional Sustainability of the Mediterranean Diet—A Scoping Review - Portugal-Nunes, Carlos; Nunes, Fernando M.; Fraga, Irene; Saraiva, Cristina; Gonçalves, Carla (Frontiers in Nutrition, 2021)
Mediterranean diet (MedDiet) is often used as an example of a sustainable diet that promotes a sustainable food system. MedDiet presents low environmental impacts, is characterized by high sociocultural food values, allows positive local economic returns, and presents major health and nutrition benefits. Previous works have not systematically examined the methodological assessment of MedDiet nutritional sustainability. Here, we review the methodological assessment of nutritional sustainability, filling a crucial gap in the literature that can inform the state of the art regarding the cross-disciplinary assessment of MedDiet nutritional sustainability. Thought a systematic search on PubMed and Scopus, 28 studies, published between 2013 and 2021, were identified. Studies that assessed the sustainability of MedDiet based on dietary consumption data, studies that explored the MedDiet sustainability resorting to dietary scenarios, studies with a mixed approach (dietary consumption and dietary scenarios) and proposals of methodological approaches to assess MedDiet nutritional sustainability were summarized. 24 studies exploring dimensions of nutritional sustainability of the MedDiet, and four proposing methodological approaches to assess MedDiet nutritional sustainability or the sustainability of MedDiet typical agro-foods were identified. From the 24 studies exploring the sustainability of MedDiet, none fully addressed the complexity of the 4 dimensions of nutritional sustainability (environmental, economic, socio-cultural and health-nutrition). One of the methodological proposals to assess MedDiet nutritional sustainability contemplated the four dimensions of nutritional sustainability, as well as one of the methodological proposals to assess the sustainability of typical agro-foods of MedDiet. Environmental sustainability was the most well studied dimension, while no study focuses on the socio-cultural dimension of sustainability. Our work reviewed for the first time the assessment of nutritional sustainability of MedDiet. To the best of our knowledge no research has been made assessing MedDiet in all the dimension of the complex concept that is nutritional sustainability. Integrating health and nutrition, environmental, economic, and socio-cultural considerations across scales and contexts can offer a more complete understanding of the opportunities and barriers to achieving nutritional sustainability not only in MedDiet but also in other dietary patterns and food products.